Performance Appraisal Process at Company X During the Program Pandemic Work From Home (WFH) - Dirama Dutha Nugraha; Andriyastuti Suratman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This internship report is related to the performance appraisal process at Company X during the pandemic or during the pandemicProgram Work From Home (WFH). Implementation of an internship from March 1 to July 1 2022 at a company in Jakarta. Company X is a fairly large domestic network provider company. This study uses a descriptive qualitative approach with observation through the use of the author's participants as apprentices in the company. The basic methods used in this internship are Observation, Interview, and Literature Study. The results of this study indicate that the performance appraisal process in Company X is divided into several processes, namely the socialization process, self assessment, and validation using theBalance Scored Card and use of the SAP systemSuccess Factors.